Chad Petroleum Sector Diagnostic Report - World Bank (World Bank, Washington, DC, 2020)
This report contains an assessment of the approach that the Republic of Chad has adopted or plans to adopt to enhance the benefits generated by the exploitation of its petroleum resources, and to manage the economic and social impact of such exploitation in a sustainable and equitable manner. Its objective is to inform the extent and prioritization of petroleum sector reforms, which might be the object of technical assistance to be provided by the World Bank and other development partners. The report focuses on the upstream part of the petroleum sector (exploration and production), where the largest fiscal and governance gains can be achieved. The report is necessarily a high-level review of geological potential, laws and regulations, and institutional capacity and organization pertaining to the petroleum sector. As such, it is not a guide on how to secure private sector investment or implement reforms. It was prepared in a short period of time combining desk research and in-country stakeholders’ consultation with the accumulated knowledge from several World Bank economic and sector studies and technical assistance operations and reflects the openness of the dialogue with the Government. Its findings are intended as background for discussion with the Authorities with the aim to identify a shared assessment of needs and priorities.